High Altitude Illness in Annapurna Circuit Trek (Journal of Tourism and Himalayan Adventures, 2019)
After 3-4 days at any point 1-16 days trekking in Annapurna circuit (max altitude=5416m), individual may show clinical manifestation of altitude illness. Despite a slow and gradual ascent, we recorded a wide range of clinical symptoms and signs. There is risk of developing high altitude illness especially at altitude above 1900m. The most common forms of high altitude illness are: Acute Mountain Sickness typically consists of headache variably accompanied by loss of appetite, nausea, vomiting, disturbed sleep, fatigue, and dizziness; High Altitude Cerebral Edema is likely a continuum of AMS, a potentially fatal illness characterized by ataxia and decreased consciousness; and High Altitude Pulmonary Edema a potentially fatal consequence of rapid ascent to high altitude characterized by incapacitating fatigue, dyspnea with minimal effort that advances to dyspnea at rest. We found out, High altitude illness will occur in non-acclimatized individuals not only after rapid ascent but also sometimes after slow ascent to high altitude. By slowing down the ascent and resting more we tried to prevent serious high altitude illness. Most of Symptoms and signs will be relieved by slowing ascent and rest. But descent is mandatory, for the treatment of the potentially fatal illnesses of high-altitude pulmonary and cerebral edema. This research provides detailed information about clinical manifestation (symptoms and signs) of altitude illnesses. After reviewing the clinical features, we will investigate the chance of occurrence of these symptoms and signs. In addition to the above, we had interesting observations and findings that we will explain.